Simultaneous Determination of Thiamine and Pyridoxine in Bulk Drug and Vitamin Tablet by HPLC-UV Method - Senol, Onur; Kadioglu, Yucel (Asian Journal of Chemistry, 2013)
Thiamine and pyridoxine which are also called vitamin B1 and B6, play crucial role in biochemical reactions in human body. HPLC-UV method for the quantitative determination of thiamine and pyridoxine in bulk drug and vitamin tablet were developed and validated in the present study. The mobile phase consisted of a mixture of water (pH: 3.5) and methanol (91:9, v/v) flowing at a flow rate of 1.0 mL/min. Calibration curve was linear between concentration range of 1-40 μg/mL. The intraday and interday precision and accuracy were between 0.8-5.4 % and 0.2-6.6 % for both analytes, respectively. Besides, the method was successfully applied to the simultaneous determination of thiamine and pyridoxine in vitamin tablet.